Does time heal all wounds? A longitudinal study of the development of posttraumatic stress symptoms in parents of survivors of childhood cancer and bereaved parents. Issue 12 (4th June 2015) - Ljungman, Lisa; Hovén, Emma; Ljungman, Gustaf; Cernvall, Martin; von Essen, Louise
Abstract: Background: A lack of longitudinal studies has hampered the understanding of the development of posttraumatic stress symptoms (PTSS) in parents of children diagnosed with cancer. This study examines level of PTSS and prevalence of posttraumatic stress disorder (PTSD) from shortly after diagnosis up to 5 years after end of treatment or child's death, in mothers and fathers. Methods: A design with seven assessments (T1–T7) was used. T1–T3 were administered during treatment and T4–T7 after end of treatment or child's death. Parents ( N  = 259 at T1; n  = 169 at T7) completed the PTSD Checklist Civilian Version. Latent growth curve modeling was used to analyze the development of PTSS. Results: A consistent decline in PTSS occurred during the first months after diagnosis; thereafter the decline abated, and from 3 months after end of treatment only minimal decline occurred. Five years after end of treatment, 19% of mothers and 8% of fathers of survivors reported partial PTSD. Among bereaved parents, corresponding figures were 20% for mothers and 35% for fathers, 5 years after the child's death. Conclusions: From 3 months after end of treatment the level of PTSS is stable. Mothers and bereaved parents are at particular risk for PTSD. The results are the first to describe the development of PTSS in parents of children diagnosed with cancer, illustrate that end of treatment is a period of vulnerability, and that a subgroup reports PTSD 5 years after end of treatment or child's death. © 2015 The Authors. Psycho‐Oncology published by John Wiley & Sons Ltd.